The Effect of Isolated and Synthetic Dietary Fibers on Markers of Metabolic Diseases in Human Intervention Studies: A Systematic Review. Issue 2 (25th July 2019) - Armet, Anissa M; Deehan, Edward C; Thöne, Julia V; Hewko, Sarah J; Walter, Jens
ABSTRACT: Observational studies provide strong evidence for the health benefits of dietary fiber (DF) intake; however, human intervention studies that supplement isolated and synthetic DFs have shown inconsistent results. Therefore, we conducted a systematic review to summarize the effects of DF supplementation on immunometabolic disease markers in intervention studies in healthy adults, and considered the role of DF dose, DF physicochemical properties, intervention duration, and the placebo used. Five databases were searched for studies published from 1990 to 2018 that assessed the effect of DF on immunometabolic markers. Eligible studies were those that supplemented isolated or synthetic DFs for ≥2 wk and reported baseline data to assess the effect of the placebo. In total, 77 publications were included. DF supplementation reduced total cholesterol (TC), LDL cholesterol, HOMA-IR, and insulin AUC in 36–49% of interventions. In contrast, <20% of the interventions reduced C-reactive protein (CRP), IL-6, glucose, glucose AUC, insulin, HDL cholesterol, and triglycerides. A higher proportion of interventions showed an effect if they used higher DF doses for CRP, TC, and LDL cholesterol (40–63%), viscous and mixed plant cell wall DFs for TC and LDL cholesterol (>50%), and longer intervention durations for CRP and glucose (50%). Half of the placebo-controlled studies used digestible carbohydrates as the placebo, which confounded findings for IL-6, glucose AUC, and insulin AUC. In conclusion, interventions with isolated and synthetic DFs resulted mainly in improved cholesterol concentrations and an attenuation of insulin resistance, whereas markers of dysglycemia and inflammation were largely unaffected. Although more research is needed to make reliable recommendations, a more targeted supplementation of DF with specific physicochemical properties at higher doses and for longer durations shows promise in enhancing several of its health effects.